8 Little Planets - Ferrie, Chris; Doyle, Elizabeth (Graphic designer) (Naperville : Sourcebooks Jabberwocky, and imprint of Sourcebooks, Inc., 2018)
"To the tune of "Ten Little Monkeys Jumping on the Bed" comes a new bedtime story from bestselling author Chris Ferrie that's sure to get little ones excited about the solar system while learning new facts about each planet!"--
Keywords: Planets -- Juvenile literature; Children's songs -- Texts; Solar system -- Juvenile literature